Results of antibiotic susceptibility testing do not influence clinical outcome in children with cystic fibrosis - Hurley, M.N.; Amin Ariff, A.H.; Bertenshaw, C.; Bhatt, J.; Smyth, Alan R. (Elsevier, 2012)
Introduction: Patients with CF experience pulmonary exacerbations. These are often initially empirically treated with intravenous antibiotics, with antibiotic choice refined after susceptibility testing.